Integrated Quality Function Deployment (QFD) Model for Dry Bulk Terminal Improvements (DBTI) in Malaysian Ports - Md. Ashlyzan, Razik; Razman, Mat Tahar; Wan Hasrulnizzam, Wan Mahmood; Norlinda, Mohd Rozar (JOEBM, 2015)
The main purpose of this paper is to apply integrated quality function deployment (QFD) for dry bulk terminal improvement from the perspectives of the customers. Firstly, the main issue of the QFD problem was made which are ‘what’ the customer required and ‘how’ to implement the problem to solutions. This two major of components to be emphasized on the house of quality (HOQ) matrices. In this research, the systematic procedures using inferential statistics which are factor analysis and correlation spearman were applying in QFD method. Factor analysis used for identifying the best group and reduced the unused items. Whereas correlation spearman used for see the relationship and strengthen each factor. The results in this study show 4 best group or criteria were identified which are loading efficiency, infrastructure improvement, time performance and dry bulk operation improvement. This four criteria is the main criteria for improvement. The using QFD method suggested the management in Port Terminal should listen the customer voice to raise the issue for solutions. How to solve the issue is based on the strategy implemented. The proposed strategy from this study can be used for the port management to identify solution in dry bulk terminal.